Clinico-Radiological study with Bronchoscopic and Histopathological Correlation of Lung Tumours (GAIMS Journal of Medical Sciences, 2024)
Lung cancer is the leading cause of cancer-related deaths worldwide. Many patients tend to have a very poor prognosis due to being diagnosed at an advanced stage especially in densely populated nations. The current study presents a case series of lung tumors. All the lung tumors presented as endobronchial mass;however histopathological diagnoses were different in each of the lung tumors after bronchoscopic guided lung mass biopsies. The first case was small cell lung cancer (SCLC) with endobronchial growth in a 64‑year‑old male. Bronchoscopy was suggestive of Left vocal cord palsy. The tiny nodule was seen over both cords with nodule present over carina. Chest CT scans revealed a well-defined irregularly shaped mass lesion with spiculated margin seen in the left lower lobe. The analysis of a biopsy specimen obtained from the tumor resulted in a diagnosis of SCLC. The second case was of non-small cell lung cancer (NSCLC) with endobronchial growth in a 77-year-old male. CECT reveals a right upper lobe malignant mass lesion with mediastinal invasion with mediastinalmetastatic nodes. Bronchoscopy revealed a right upper lobe malignant mass. Histopathological examinationrevealed features consistent with NSCLC of Squamous cell carcinoma. The third case was a 58-year-old male whose CECT Thorax revealed a malignant pulmonary mass lesion in the left hilar region. Bronchoscopy was suggestive of endobronchial growth present in Left main bronchus around 1.5 cm from the carina. Tissue taken from the Left Hilar mass showed features of NSCLC-Adenocarcinoma carcinoma of the lung.